A polysaccharide from Sargassum pallidum reduces obesity in high-fat diet-induced obese mice by modulating glycolipid metabolism. Issue 13 (16th June 2022) - Yuan, Dan; Huang, Qiang; Li, Chao; Fu, Xiong
Abstract : Sargassum pallidum polysaccharide (SPP) has potential to be used as a promising dietary supplement for ameliorating obesity. Abstract : Sargassum pallidum polysaccharide (SPP) has been shown to have antioxidant, hypoglycemic, and hypolipidemic effects. However, the anti-obesity mechanism of SPP in obese mice remains unclear. This study aimed to investigate the anti-obesity effect and mechanism of SPP in obese mice induced by a high-fat diet (HFD). The model and experimental groups were fed with a HFD, and the experimental groups were simultaneously orally treated with degraded SPP (D-SPP) with dosages of 50, 100, and 200 mg kg −1 for 8 weeks, respectively. The results showed that oral administration of D-SPP not only dramatically suppressed body weight gain and reduced the fasting blood glucose level, but also lowered the levels of serum and hepatic lipids in HFD-induced obese mice. Histopathological analysis showed that D-SPP significantly prevented liver fat accumulation and reduced white adipose hypertrophy and adipocyte size. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis indicated that D-SPP intervention significantly down-regulated the relative expressions of adipogenesis genes. Specifically, the peroxisome proliferator-activated receptors-γ (PPAR-γ), sterol regulatory element-binding protein-1 (Srebp-1c), acetyl-CoA carboxylase-1(ACC1) and fatty acid synthase (FAS) in the liver of obese mice were decreased by 68, 53, 73, and 78%, respectively. These findings suggest that D-SPP might potentially be used as a promising dietary supplement for ameliorating obesity.